2010
DOI: 10.1111/j.1740-8261.2010.01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Features of Discospondylitis in Dogs

Abstract: The diagnosis of discospondylitis is based mainly on diagnostic imaging and laboratory results. Herein, we describe the magnetic resonance imaging (MRI) findings in 13 dogs with confirmed discospondylitis. In total there were 17 sites of discospondylitis. Eleven (81.1%) of the dogs had spinal pain for >3 weeks and a variable degree of neurologic signs. Two dogs had spinal pain and ataxia for 4 days. Radiographs were available in nine of the dogs. In MR images there was always involvement of two adjacent verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(109 citation statements)
references
References 30 publications
4
99
2
1
Order By: Relevance
“…13,14,[20][21][22][23][24][25] Similarly, MRI findings were consistent with those previously reported for dogs with spinal epidural empyema, including hyperintense extradural lesions on T2-weighted images and contrast enhancement in a diffuse or ring-like pattern on T1-weighted images after IV administration of gadolinium-based contrast medium. 5,13,18,19 However, lesions on precontrast T1-weighted images varied from mildly hyperintense (dogs 1, 2, and 3) to hypointense (dogs 4 and 5). In veterinary patients, lesions associated with spinal epidural empyema have previously been reported to be hypointense on T1-weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14,[20][21][22][23][24][25] Similarly, MRI findings were consistent with those previously reported for dogs with spinal epidural empyema, including hyperintense extradural lesions on T2-weighted images and contrast enhancement in a diffuse or ring-like pattern on T1-weighted images after IV administration of gadolinium-based contrast medium. 5,13,18,19 However, lesions on precontrast T1-weighted images varied from mildly hyperintense (dogs 1, 2, and 3) to hypointense (dogs 4 and 5). In veterinary patients, lesions associated with spinal epidural empyema have previously been reported to be hypointense on T1-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Experimental studies 27,29 have suggested that compression plays a larger role than ischemia, because neurologic improvement is observed after surgical decompression, and in dogs, diskospondylitis results in neurologic deficits when granulation tissue extends into the spinal canal, causing compression. 18 However, a study 1 examining spinal cord compression associated with diskospondylitis found that the degree of spinal cord compression did not correlate with the severity of neurologic signs and the outcome was similar between dogs treated with decompressive surgery and those managed medically. In the present case series, one of the dogs with the most severe neurologic deficits had a minimally compressive lesion (dog 2), and another dog (dog 4) with no deep pain sensation in the pelvic limbs nevertheless made a full recovery without surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous aspiration of disc or biopsy may have a higher success range. 4 Hematogenous spread is responsible for a large number of discospondylitis lesions. A less common route of infection is by penetrating wounds or by migrating plant material.…”
Section: Brief Communicationmentioning
confidence: 99%
“…Magnetic resonance imaging, the golden standard in diagnosing pathological changes in the spine, supports 3D visualization, diagnosis of epidural and intradural diseases and earlier detection of changes than in conventional radiography (Carrera et al 2011). The changes visible in radiographic images, such as narrowing of the space between intervertebral…”
Section: Introductionmentioning
confidence: 98%